Organocatalytic Synthesis of Substituted Vinylene Carbonates. Issue 22 (14th September 2021) - Onida, Killian; Haddleton, Alice J.; Norsic, Sébastien; Boisson, Christophe; D'Agosto, Franck; Duguet, Nicolas
Abstract: The organocatalytic synthesis of substituted vinylene carbonates from benzoins and acyloins was studied using diphenyl carbonate as a carbonyl source. A range of N ‐Heterocyclic Carbene (NHC) precursors were screened and it was found that imidazolium salts were the most active for this transformation. The reaction occurs at 90 °C under solvent‐free conditions. A wide range of substituted vinylene carbonates (symmetrical and unsymmetrical, aromatic or aliphatic), including some derived from natural products, were prepared with 20–99% isolated yields (24 examples). The reaction was also developed using thermomorphic polyethylene‐supported organocatalysts as recoverable and recyclable species. The use of such species facilitates the workup and allows the synthesis of vinylene carbonates on the preparative scale (>30 g after 5 runs). Abstract :